Trade and Civil Conflict : Revisiting the Cross-Country Evidence - Cali, Massimiliano; Mulabdic, Alen (World Bank Group, Washington, DC, 2014)
This paper revisits and expands the evidence on the impact of trade shocks on intra-state conflict with a large sample of developing countries in the 1960-2010 period. The results suggest that increases in the prices of a country's exported commodities raise the country's risk of civil conflict and its duration. The effect on conflict risk is mainly driven by the price of point-source commodities, in line with the rapacity effect theory of conflict. However, the paper does not find support for the opportunity cost theory via exported commodities. The analysis also finds that intense trading with contiguous countries is associated with lower duration of intra-state conflict, consistent with the idea that such trade reduces the incentive of contiguous countries to fuel conflict in their neighbor. Trading with neighbors is also associated with a lower risk of conflict, when such trade occurs under trade agreements. By contrast, neither imported commodity prices nor the economic cycle in export markets appears to exert any influence on the probability or duration of conflict. The paper identifies several conditions under which changes in the value of exported commodities cease to matter for conflict probability.